Enhanced Electro-Static Modulation of Ionic Diffusion through Carbon Nanotube Membranes by Diazonium Grafting Chemistry - Majumder, Mainak (2008)
A membrane structure consisting of an aligned array of open ended carbon nanotubes (~ 7 nm i.d.) spanning across an inert polymer matrix allows the diffusive transport of aqueous ionic species through CNT cores. The plasma oxidation process that opens CNTs tips inherently introduces carboxylic acid groups at the CNT tips, which allows for a limited amount of chemical functional at the CNT pore entrance. However for numerous applications, it is important to increase the density of carboxylic acid groups at the pore entrance for effective separation processes. Aqueous diazonium based electro-chemistry significantly increases the functional density of carboxylic acid groups. pH dependent dye adsorption-desorption and interfacial capacitance measurements indicate ~ 5–6 times increase in functional density. To further control the spatial location of the functional chemistry, a fast flowing inert liquid column inside the CNT core is found to restrict the diazonium grafting to the CNT tips only. This is confirmed by the increased flux of positively charged Ru(bi-py)(3)(+2) with anionic functionality. The electrostatic enhancement of ion diffusion is readily screened in 0.1(M) electrolyte solution consistent with the membrane pore geometry and increased functional density.